2010
DOI: 10.1007/s11904-010-0043-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of HIV Among Injecting and Non-injecting Drug Users: Current Trends and Implications for Interventions

Abstract: Injecting drug use is a major driver of HIV infections in Eastern Europe, the Commonwealth of Independent States, North Africa, the Middle East, and many parts of Asia and North America. We provide a global overview of the epidemiology of HIV infection among drug users and present current drug use trends that may constitute important epidemic drivers. We describe trends in ethnic disparities among injecting drug using (IDU) populations in the United States, and comment upon how these trends may now be changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
201
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(213 citation statements)
references
References 41 publications
4
201
0
8
Order By: Relevance
“…The study by Sordo et al [2] provides the first review and meta-analysis of prospective observational cohort studies on initiation into drug injection among vulnerable populations. The major finding was a strong relationship between the incidence of initiation to injecting and the length of follow-up time.…”
Section: Reducing Bias In Prospective Observa-tional Studies Of Drug mentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Sordo et al [2] provides the first review and meta-analysis of prospective observational cohort studies on initiation into drug injection among vulnerable populations. The major finding was a strong relationship between the incidence of initiation to injecting and the length of follow-up time.…”
Section: Reducing Bias In Prospective Observa-tional Studies Of Drug mentioning
confidence: 99%
“…In the last 30 years there have been several worrisome developments in injection drug use globally, including the continued spread of drug injection to new countries [1], HIV and viral hepatitis outbreaks among people who inject drugs (PWID) in eastern Europe and Asia, among other regions [2], and the adoption of methamphetamine and opioid prescription medications as injectable drugs [3]. However, Sordo et al's (2015) excellent systematic review and meta-analysis published in this issue of Addiction identified only nine cohort studies over this time-frame that provide information on injection initiation incidence [4].…”
mentioning
confidence: 99%
“…1 Globally, injecting drug use accounts for a third of new HIV infections outside sub-Saharan Africa, 2 with the highest drug-related incidence occurring in Asia and Eastern Europe. 2,3 Of the 16 million people who inject drugs (PWID) worldwide, 3 million are HIV-positive.…”
mentioning
confidence: 99%
“…NIDU exhibit several risk behaviors for acquiring HIV, such as polysubstance use, inconsistent use of condoms, sex work, and multiple sexual partners (8)(9)(10). Studies have shown elevated prevalence of HIV infection among NIDU worldwide, ranging from 3.7% in México to 16.0% in the United States of America (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%